Contribution of leg muscle explosive power and leg length with the results of the straddel-style high jump in SMA Negeri 6 Pekanbaru - Jaka Sunardi; Raffly Henjilito (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2020)
The purpose of this study is to determine the contribution of leg muscle explosive power and leg length to the results of straddle-style high jumping at SMA Negeri 6 Pekanbaru students. This type of research is correlation. Population and sample in this study were all students of class X IPS 2, 25 people and the sample of 15 students. The instruments of this study include the leg muscle explosive test that is vertical jump, leg length test using a meter and straddle style high jump test. The data analysis technique is the correlation value test. Based on the results of the research that has been done, it can be concluded that there is a contribution of leg muscle explosive power (X1) and high jumping straddle force results in 6 Pekanbaru (Y) High School (Y) students, where rcount = 0.53 At significant level 5% is found rtable = 0.514, thus rcount rtable or 0.53 0.514. There is a contribution of leg length (X2) and straddle force high jump results in 6 Pekanbaru (Y) High School students, which is found to be r = 0.53 At a significant level of 5% found rtable = 0.514, thus rcount rtable or 0, 530.514. There is a contribution of leg muscle explosive power (X1) and leg length (X2) with the high jumping result of straddle force in high school 6 Pekanbaru (Y) high school students, which is found to be counted = 0.699 At a significant level of 5% found rtable = 0.514, thus rcount r table or 0.699 0.514 in the strong category. Kontribusi daya ledak otot tungkai dan panjang tungkai dengan hasil lompat tinggi gaya straddel pada siswa SMA Negeri 6 Pekanbaru AbstrakTujuan dari penelitian ini yaitu untuk mengetahui kontribusi daya ledak otot tungkai dan panjang tungkai dengan hasil lompat tinggi gaya straddle pada siswa SMA Negeri 6 Pekanbaru. Jenis penelitian ini ialah korelasi. Populasi serta sampel pada penelitian ini adalah seluruh siswa kelas X IPS 2 yaitu 25 orang serta sampelnya siswa putra yang berjumlah 15 orang. Instrument penelitian ini antara lain tes daya ledak otot tungkai yaitu vertical jump, tes panjang tungkai menggunakan meteran dan tes lompat tinggi gaya straddle. Teknik analisis datanya yaitu uji nilai korelasi. Berdasarkan dari hasil penelitian yang telah di lakukan maka dapat di simpulkan bahwa terdapat kontribusi daya ledak otot tungkai (X1) dan hasil lompat tinggi gaya straddle pada siswa SMA Negeri 6 Pekanbaru (Y), di mana di dapati rhitung = 0,53 Pada taraf signifikan 5% didapati rtabel = 0,514, dengan demikian rhitung rtabel atau 0,53 0,514. Terdapat kontribusi panjang tungkai (X2) dan hasil lompat tinggi gaya straddle pada siswa SMA Negeri 6 pekanbaru (Y), dimana di dapati rhitung = 0,53 pada taraf signifikan 5% didapati rtabel = 0,514, dengan demikian rhitung rtabel atau 0,53 0,514. Terdapat kontribusi daya ledak otot tungkai (X1) dan panjang tungkai (X2) dengan hasil lompat tinggi gaya straddle pada siswa SMA Negeri 6 Pekanbaru (Y), dimana di dapati rhitung = 0,699 pada taraf signifikan 5% didapati rtabel = 0,514, dengan demikian rhitung rtabel atau 0,699 0,514 dalam kategori kuat.